Comparison of Surgical Techniques as a Prognostic Factor on Success Rate in Chronic Otitis Media - Mohammad Faramarzi; Sareh Roosta; Amineh Behzadi (Fasa University of Medical Sciences, 2019)
Background & Objective: Review of literature show that there are contradictory opinions, regarding the surgical technique act as a prognostic factor in graft success rate. Therefore, the researchers decided to consider the topic by reviewing the literatures and gathering their ten years experiences information regarding this issue. Materials & Methods: This retrospective study was carried out on ears undergoing chronic otitis media surgeries. Five hundred and five ears underwent chronic otitis media surgeries were evaluated. We analyzed 225 tympanoplasty (44.6%), 93 canal walls up mastoidectomy (18.4%) and 187 canal wall down mastoidectomy (37%). The primary outcome was anatomic results (graft success rate in each surgical technique) and the secondary outcome was hearing outcomes. Results: Total graft success rate was found in 460 ears (91.1%). Also graft success rate in tympanoplasty, canal wall up mastoidectomy and canal wall down mastoidectomy groups were observed in 201 ears (89.3%), 81 ears (87.1%) and 178 ears (95.2%), respectively. But there was not significant statistical difference between different methods (P=0.14). The mean post-operation air-bone gap gains in these three surgical techniques were 7.8, 11.1 and 4.3 dB, consecutively Conclusion: However, our results showed that the overall graft success rate was in an acceptable range and graft success rate in canal wall down mastoidectomy was more than tympanoplasty and canal wall up mastoidectomy, but the surgical technique was not a prognostic factor in graft success rate.